RETRACTED: How Multi-Dimensional Local Government Competition Impacts Green Economic Growth? A Case Study of 272 Chinese Cities - Su, Xufeng; Liu, Guangliang; Xu, Yang; Ge, Wenfeng; Shen, Bing; Ran, Qiying; Zhou, Hui (Frontiers in Environmental Science, 2022)
Green economic growth is an unavoidable choice for China's development model, while the government-led Chinese economic development system determines that local government competition may have an essential impact on green economic growth. For this purpose, this study employs data on Chinese 272 prefecture-level cities and the system generalized method of moments (SYS-GMM) model to investigate the impact of multi-dimensional local government competition (ecological competition, service competition, economic competition, and comprehensive competition) on green economic growth. The empirical results reveal that local government competition significantly influences green economic growth, in which economic competition significantly inhibits green economic growth, and ecological competition, service competition, and comprehensive competition positively influences green economic growth. The influence mechanism indicates that economic competition, ecological competition, service competition, and comprehensive competition significantly affect green economic growth through economic agglomeration and industrial structure upgrading, respectively. Moreover, the impact of multi-dimensional local government competition on green economic growth shows significant temporal and regional heterogeneity. Therefore, policymakers should further develop a multi-dimensional local government competition target system for local government officials and moderately enhance both ecological competition and service competition that is oriented to green economic growth.